Relationship Between Knowledge & Attitudes of Cleaning Staff Towards Medical Waste Management at Pidie Jaya Regional Hospital, Pidie Jaya Regency: Hubungan Pengetahuan & Sikap Petugas Kebersihan Terhadap Pengelolaan Limbah Medis di RSUD Pidie Jaya Kabupaten Pidie Jaya - Armiatin; Azizah; Nasiatul Aisyah Salim (JOHAR (Journal of Hospital Administration Research), 2024)
Medical waste management is very important because medical waste is dangerous and therefore poses a serious threat not only to patients and health workers but also to society and the environment. This research aims to determine the relationship between knowledge & attitudes of cleaning staff regarding medical waste management at Pidie Jaya Hospital, Pidie Jaya Regency. This type of research is descriptive analytic with a cross sectional approach. The populations in this study was 25 cleaning staff at Pidie Jaya Regional Hospital. The sampling technique uses total sampling. Data collection uses a questionnaire. Data analysis used the chi square statistical test. The results of the research explain that there is a relationship between the knowledge of cleaning staff and medical waste management at Pidie Jaya Regional Hospital, Pidie Jaya Regency. Apart from that, there is a relationship between the attitude of cleaning staf towards medical waste management at Pidie Jaya Hospital, Pidie Jaya Regency. So that good knowledge and attitudes among cleaning staff will ensure good medical waste management in hospitals.